2009
DOI: 10.2147/cia.s5797
|View full text |Cite
|
Sign up to set email alerts
|

Eggshell membrane: A possible new natural therapeutic for joint and connective tissue disorders. Results from two open-label human clinical studies

Abstract: Background:Natural Eggshell Membrane (NEM®) is a novel dietary supplement that contains naturally occurring glycosaminoglycans and proteins essential for maintaining healthy joint and connective tissues. Two single center, open-label human clinical studies were conducted to evaluate the efficacy and safety of NEM® as a treatment for pain and inflexibility associated with joint and connective tissue disorders.Methods:Eleven (single-arm trial) and 28 (double-arm trial) patients received oral NEM® 500 mg once dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
60
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 21 publications
7
60
0
2
Order By: Relevance
“…And almost 20% of the study population experienced a 50% improvement in pain-related questions by the end of the study (60 days) (not shown). These results align well with results from previous clinical studies of NEM ® that were conducted in the U.S. [6,7].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…And almost 20% of the study population experienced a 50% improvement in pain-related questions by the end of the study (60 days) (not shown). These results align well with results from previous clinical studies of NEM ® that were conducted in the U.S. [6,7].…”
Section: Discussionsupporting
confidence: 90%
“…In previous trials with NEM ® [6,7], the standard deviation for the study subjects for pain (within the inclusion range of this study) averaged 34.6%. We hoped to be able to detect a 1.5 point difference from baseline within the 10-point Likert scale.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The eggshell membrane is one of the food supplements that have had very good results in this sense [2][3][4][5]. Eggshell membrane is comprised of a large part of collagen, mainly type I, V and X [6][7][8]; glycosaminoglycans (hyaluronic acid, chondroitin sulfate and different proteins that are involved in the antiinflammatory and immune system regulation ability of the eggshell membrane (lysozyme, ovotransferrin, ovocleidin-17 and ovocleidin-116) [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely studied because of its remarkable properties, which could be utilized in catalysis, adsorption of heavy metals [Au(I) and Au(III)] (Ishikawa et al 2002), dyes (malachite green) (Chen et al 2012) and organics (eosin B) (Ning and Tao 2011), biosensors (immobilized enzyme glucose oxidase) (Zheng et al 2011), sulfonates (Wang et al 2010) and fluorides (Lunge et al 2012). In addition, EMS has been also used in medical industries as a possible new effective and safe therapeutic option for the treatment of pain and inflexibility associated with joint and connective tissue (JCT) disorders (Ruff et al 2009). ESM has found applications in ophthalmology as a cheap and versatile eye model which could be used during vitreous surgery training (Benson et al 2012).…”
Section: Introductionmentioning
confidence: 99%